Variations in the Accommodative and Vergence Responses, in addition to Visual Discomfort, in University Optometry Students Following Prolonged Near Work - Bhattacharya, Bidisha; Arvind, Anitha (Journal of Neonatal Surgery, 2025)
Purpose: To assess the accommodative and vergence response changes along with visual discomfort in university optometry student population after a prolonged near work. Methods:This study was done between July 1 and November 30, 2024, at Delhi Skill & Entrepreneurship University. Sixty participants with refractive error (+/- 0.50DS to +/- 3.00DS) and no prior history of orthoptics exercises were included. The Visual discomfort questionnaire (VDQ) was administered at baseline and after 7 hours of near work to evaluate asthenopic symptoms. Accommodative and vergence parameters were measured clinically pre- and post-classes. Results: Of the 60 students, 23 were male (age range of 18 to 25 years). The 47% (n=28) had Emmetropia and 53% (n=32) had Ametropia. Accommodative parameters include Monocular Estimation method (mean difference, 1.15 ± 0.10 diopters), Accommodative amplitudes (mean difference, 2.71 ± 0.62 diopters) and both Monocular and Binocular Accommodative Facility measurements (mean difference, 3.29 ± 0.19cpm) reported statistically significant differences (P<0.001) between the two measurements for both Emmetropes and Ametropes group. Vergence parameters were statistically significant (p>0.05). At baseline, 60% reported no discomfort, 25% reported discomfort occasionally, 12% often, and 2% always. Post-classes discomfort increased occasionally to 32%, but it was not statistically significant (p> 0.05). Conclusion: Our study shows a significant change in accommodative variables for both groups (Emmetropes & Ametropes). VDQ scores shows no statistically significant differences between pre and post near work. These findings suggest that prolonged near work impacts accommodative function but do not significantly alter self-reported discomfort levels